INTERAKSI EDUKATIF GURU PAI DAN ORANG TUA DALAM PENINGKATAN TANGGUNG JAWAB BELAJAR SISWA SD MUHAMMADIYAH 11 MEDAN - Apriani, Suci; Arsyad, Junaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the role of educational interactions between Islamic Religious Education (PAI) teachers and parents in increasing students' learning responsibilities at SD Muhammadiyah 11 Medan. The research method used is a qualitative method with a case study approach. Data collection was carried out through interviews, observation and documentation involving PAI teachers, parents and students. The research results show that effective educational interactions between PAI teachers and parents contribute significantly to increasing student learning responsibility. PAI teachers play an important role in providing academic guidance and religious values, while parents support the learning process through supervision and motivation at home. The collaboration between these two parties creates a conducive learning environment for students to develop a sense of responsibility for their academic assignments. The conclusion of this research emphasizes the importance of synergy between teachers and parents in supporting student learning success.